2018
DOI: 10.1002/lt.24964
|View full text |Cite
|
Sign up to set email alerts
|

Next generation sequencing in pediatric hepatology and liver transplantation

Abstract: Next generation sequencing (NGS) has revolutionized the analysis of human genetic variations, offering a highly cost-effective way to diagnose monogenic diseases (MDs). Because nearly half of the children with chronic liver disorders have a genetic cause and approximately 20% of pediatric liver transplantations are performed in children with MDs, NGS offers the opportunity to significantly improve the diagnostic yield in this field. Among the NGS strategies, the use of targeted gene panels has proven useful to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 64 publications
1
52
0
4
Order By: Relevance
“…Moreover, Rohanizadegan et al reported the usefulness of rapid whole‐exome sequencing to diagnose a case of neonatal NPC . These next‐generation sequencing techniques have been also developing in recent years, and they will help us to obtain accurate and rapid diagnosis in complex disease like NALF, lysosome disease, or metabolic disorders in the near future …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Rohanizadegan et al reported the usefulness of rapid whole‐exome sequencing to diagnose a case of neonatal NPC . These next‐generation sequencing techniques have been also developing in recent years, and they will help us to obtain accurate and rapid diagnosis in complex disease like NALF, lysosome disease, or metabolic disorders in the near future …”
Section: Discussionmentioning
confidence: 99%
“…The glucosylceramide synthase inhibitor miglustat, which was developed for the treatment of lysosome disease, has been shown to delay or improve the neurological symptoms, extend survival, maintain the cellular structure of the cerebellum, and suppress the accumulation of gangliosides in the brain in NPC patients or animal models . Multiple clinical trials, particularly in adults, have demonstrated efficacy of miglustat inhibiting the progression of, or improving neurological symptoms . Furthermore, miglustat has been shown to pass through the blood‐brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Other independent studies have consistently reported WES diagnostic rates of 20% or higher . Furthermore, we and others have successfully combined WES with deep phenotyping (i.e., detailed characterization of each patient's phenotypic features) to identify the underlying genetic defects in infants and children with idiopathic liver diseases, including children with liver failure of indeterminate etiology . Astute clinical annotation (i.e., comprehensive phenotype description of the patient) is central to harnessing the maximal potential of genomic data .…”
Section: Where Could Hepatologists Be Missing Liver‐related Genetic Tmentioning
confidence: 95%
“…Children with chronic liver disease represent an enriched population with single gene disorders; therefore, many of the known genetic causes of liver diseases present during childhood . Thus, genetic liver disorders are traditionally associated with pediatric hepatology practice, in which NGS for timely diagnosis has been progressively embraced over the past years . There is extensive experience of application of WES in nonhepatic pediatric disorders.…”
Section: Where Could Hepatologists Be Missing Liver‐related Genetic Tmentioning
confidence: 99%
“…In distinction, cholangiopathies such as biliary atresia, ABCB4 and DCDC2 deficiencies, as well as ALGS often present with elevated GGT levels. With the increasing worldwide use of modern next generation sequencing, the roles for liver biopsy in the evaluation are becoming less essential …”
Section: Diagnosis Of Pediatric Cholestasismentioning
confidence: 99%